Archaeology of the Teufelsberg - Cocroft, Wayne, author.
1 online resource.
Keywords: "For over fifty years, the white radomes of the Teufelsberg have been one of Berlin's most prominent landmarks. For half of this time the city lay over 100 miles behind an 'Iron Curtain' that divided East from West, and was surrounded by communist East Germany and the densest concentration of Warsaw Pact military forces in Europe. From the vantage point high on the Teufelsberg, British and American personnel constantly monitored the electronic emissions from the surrounding military forces, as well as high-level political intelligence. Today, the Teufelsberg stands as a contemporary and spectacular ruin, representing a significant relic of a lost cyber space of Cold War electronic emissions and espionage. Based on archaeological fieldwork and recently declassified documents this book presents a new history of the Teufelsberg and other Western intelligence gathering sites in Berlin. At a time when intelligence gathering is once more under close scrutiny, when questions are being asked about the intelligence relationship between the US and Germany, and amidst wider debate about the USA's National Security Agency (NSA) intelligence programmes, sites like the Teufelsberg raise questions that appear both important and timely"--